Proteins Associated with Salinity Adaptation of the Dinoflagellates: Diversity and Potential Involvement in Species Evolution - Nataliia V. Annenkova (Diversity)
Protists inhabit marine, brackish and fresh waters. The salt barrier plays an important role in the origin of their diversity. Salinity tolerance differs among species and sometimes even among different strains of the same species, indicating local adaptation. Dinoflagellates from the Apocalathium genus are represented by at least four species, which originated via rapid and recent radiation. Water salinity was suggested as one of the key factors for this radiation. A previous study found RNA transcripts, which belong exclusively to saline strains of Apocalathium, and were absent in its freshwater strains. In the present paper, the diversity of these transcripts and their orthologs from marine and freshwater protists were analysed using bioinformatic approaches. First, it was found that these specific transcripts translated to the proteins, which are important for osmoregulation (e.g., transport of various compounds including glycine betaine, regulation of microtubule organisation, post transcriptional modifications). This supports the idea that speciation within Apocalathium resulted in the loss of osmoregulatory genes by freshwater species. Second, protein distribution was not highly species specific, because their orthologs were found in different dinoflagellates and were relatively common in other phototrophic protists, though the sequences were highly variable. Proteins from 13 orthogroups were absent or very rare in studied freshwater genomes and transcriptomes. They could play a specific role in protists salinity tolerance. Third, detailed phylogenetic analyses of betaine-like transporter and chloride transmembrane transporters, which probably are one of the key proteins associated with salinity tolerance, revealed high levels of multiple and variable copies that were not eliminated from the genome during the evolution. The expression of their genes could be important in the adaptation of dinoflagellates to salinity changes, as it was already shown for some other protists.